EFFECT OF SALINISATION OF SOIL ON GROWTH AND MACRO- AND MICRO-NUTRIENT ACCUMULATION IN SEEDLINGS OF BUTEA MONOSPERMA (FABACEAE) - Damjibhai Hirpara, Ketan; Jamnadas Ramoliya, Prakash; Dahyabhai Patel, Ashish; Nath Pandey, Amar (Anales de Biología, 2005)
Effects of salinisation of soil on emergence, seedling growth and mineral accumulation of Butea monosperma Taub. (Fabaceae) were studied. Sodium chloride (NaCl) was added to the soil and salinity was maintained at 0.3, 1.9, 3.9, 6.2, 8.2, 10.2, 12.2 and 13.8 dSm-1 Salinity caused reduction in water content of all tissues (leaves, stems, tap roots and lateral roots) that resulted in internal water deficit to plants. Increasing salt stress impaired succulent feature of tap roots. Succulence is an adaptation of this tree species to salt stress because it temporarily puts off the setting of severe water deficit induced by salt stress. Sodium content significantly increased in leaves and stems and there was no effective mechanism to block Na transfer to shoot tissues. Potassium content also significantly increased in tissues, however, Na was transferred to the tissues in greater proportion than K. Nitrogen and phosphorus contents significantly decreased in all tissues in response to salinisation of soil. Changes in tissues and whole plant accumulation patterns of the other elements tested, as well as possible mechanisms for avoidance of Na toxicity in this tree species during salinisation, are discussed.